2021
DOI: 10.1080/2162402x.2021.1907912
|View full text |Cite
|
Sign up to set email alerts
|

CD80 expression is upregulated by TP53 activation in human cancer epithelial cells

Abstract: CD80 is recognized as one of the most potent costimulatory molecules by which immune cells limit cancer progression; however, the current understanding of the regulation of its expression on human tumor cells is limited. The TP53 tumor suppressor plays a critical role in cancer and its significant role in the control of immune responses is emerging. Here, we evaluated the role of TP53 as a regulator of CD80 expression in human cancer cells. A set of well-known TP53–reactivating compounds were used on TP53-wild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…A previous study reported that the CD80 expression was higher in MDA-MB-468, MCF-7, and MDA-MB-231 breast cancer cells than in normal MCF10A cells ( Li et al, 2020 ). Evidence supported that pharmacological activation of TP53 can promote the CD80 expression in human cancer cells originating from the epithelium ( Scarpa et al, 2021 ). Previous studies have showed that the CD80 expression is lower in several cancer cells, and the loss of CD80 alone promotes their ability to escape the attack from the immune system and imparts energy and apoptosis in tumor-infiltrating T cells ( Tirapu et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that the CD80 expression was higher in MDA-MB-468, MCF-7, and MDA-MB-231 breast cancer cells than in normal MCF10A cells ( Li et al, 2020 ). Evidence supported that pharmacological activation of TP53 can promote the CD80 expression in human cancer cells originating from the epithelium ( Scarpa et al, 2021 ). Previous studies have showed that the CD80 expression is lower in several cancer cells, and the loss of CD80 alone promotes their ability to escape the attack from the immune system and imparts energy and apoptosis in tumor-infiltrating T cells ( Tirapu et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…TEV carry both CTLA-4 and its ligands CD80/CD86 [ 127 , 128 , 129 , 130 ]. It has been proposed that the expression of CD80/CD86 in TEV interferes with CTL activity by binding to CTLA-4 [ 128 , 129 ].…”
Section: Tev Characterisationmentioning
confidence: 99%
“…TEV carry both CTLA-4 and its ligands CD80/CD86 [ 127 , 128 , 129 , 130 ]. It has been proposed that the expression of CD80/CD86 in TEV interferes with CTL activity by binding to CTLA-4 [ 128 , 129 ]. Circulating TEV carrying CTLA-4 were also detected in cancer patients, and their concentration correlated with a poor outcome [ 127 , 130 ].…”
Section: Tev Characterisationmentioning
confidence: 99%
“…Another immune checkpoint pathway that could negatively regulate T-cell anti-tumor function in the setting of cancer is cytotoxic T-lymphocyte-associated antigen 4 (CTLA-4) and macrophage Clever-1. CTLA-4 upregulation and binding with CD80/CD86 promotes T cell anergy (149), and cancer cells (150)(151)(152) and TAMs (153) have been shown to express CD80 and CD86. The macrophage Clever-1, a multifunctional adhesion and scavenger receptor expressed by immunosuppressive macrophages and TAMs, has also been shown to have inhibitory effect on CD8 + T cells (154).…”
Section: Immunosuppressionmentioning
confidence: 99%